Theoretical background of human posture recognition - Htike, Kyaw Kyaw; Khalifa, Othman Omran; Khan, Sheroz; Lai, Weng Kin (IIUM Press, 2011)
Human posture refers to the arrangement of the body and its limbs. According to Oxford Dictionary (2009), posture is defined as the particular position of the body and the way in which a person holds his or her body. There are several agreed types of human postures such as standing, sitting. squatting, lying, kneeling and other unusual positions such as standing on the anns, standing on the head, being "on all fours" and etc